2007
DOI: 10.1029/2007gl031932
|View full text |Cite
|
Sign up to set email alerts
|

Empirical transfer functions: Application to determination of outermost core velocity structure using SmKS phases

Abstract: [1] SmKS waves provide good resolution of outer-core velocity structure, but are affected by heterogeneity in the D 00 region. We have developed an Empirical Transfer Function (ETF) technique that transforms a reference pulse (here, SmKS) into a target waveform (SKKS) by: (1) timewindowing the respective pulses, (2) applying Wiener deconvolution, and (3) convolving the output with a Gaussian waveform. Common source and path effects are implicitly removed by this process. We combine ETFs from 446 broadband seis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…However, the conclusions of various studies are not consistent. For example, Alexandrakis and Eaton (2007) exploited the Empirical Transfer Function technique to precisely measure SmKS differential travel times and found no evidence for stratification, consistent with some other SmKS studies (e.g., Alexandrakis & Eaton, 2010;Souriau & Poupinet, 1991a). In contrast, other reports support a layer with lower Vp than that of PREM in the outermost core (e.g., Eaton & Kendall, 2006;Garnero et al, 1993;Helffrich & Kaneshima, 2010;Kaneshima & Matsuzawa, 2015;Kaneshima, 2018;Tanaka, 2004Tanaka, , 2007Tang et al, 2015), although the thickness and amplitude of the Vp anomaly varies from one study to another.…”
Section: Introductionsupporting
confidence: 81%
“…However, the conclusions of various studies are not consistent. For example, Alexandrakis and Eaton (2007) exploited the Empirical Transfer Function technique to precisely measure SmKS differential travel times and found no evidence for stratification, consistent with some other SmKS studies (e.g., Alexandrakis & Eaton, 2010;Souriau & Poupinet, 1991a). In contrast, other reports support a layer with lower Vp than that of PREM in the outermost core (e.g., Eaton & Kendall, 2006;Garnero et al, 1993;Helffrich & Kaneshima, 2010;Kaneshima & Matsuzawa, 2015;Kaneshima, 2018;Tanaka, 2004Tanaka, , 2007Tang et al, 2015), although the thickness and amplitude of the Vp anomaly varies from one study to another.…”
Section: Introductionsupporting
confidence: 81%
“…Seismological constraints have been so far inconclusive. However, recent seismological results using outermost core waveforms seem to be consistent with the existence of a low density layer of about 100 km thickness (Alexandrakis and Eaton, 2007;Tanaka, 2007) It has been confirmed that Mercury has a liquid iron core (Margot et al, 2007). Furthermore, it is likely that Mercury's weak intrinsic magnetic field is generated by a dynamo in its liquid outer core.…”
Section: Terrestrial Planetsmentioning
confidence: 88%